2020
DOI: 10.3390/nano10061038
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz Metamaterial with Multiple Resonances for Biosensing Application

Abstract: A sickle-shaped metamaterial (SSM) based biochemical sensor with multiple resonances was investigated in the terahertz frequency range. The electromagnetic responses of SSM were found to be four resonances, namely dipolar, quadrupolar, octupolar and hexadecapolar plasmon resonances. They were generated from the interactions between SSM and perpendicularly incident terahertz waves. The sensing performances of SSM-based biochemical sensors were evaluated by changing ambient environments and analyte varieties. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(25 citation statements)
references
References 27 publications
0
24
0
1
Order By: Relevance
“…One study demonstrated the use of biosensor built using metamaterial and semiconductor that measure refractive index of analyte at far infrared 27 . Metamaterial can also be applied in various applications: as dual tunable absorbers 28 of different shapes such as chevron 29 and wrench 30 ; chemical sensing 31 ; infrared filter 32 , 33 ; tunable polarizer 34 , microelectromechanical devices 35 ; and polarization-insensitive devices 36 . Nanoparticle can also be used in development of biosensor for applications such as medical diagnostic devices 37 .…”
Section: Introductionmentioning
confidence: 99%
“…One study demonstrated the use of biosensor built using metamaterial and semiconductor that measure refractive index of analyte at far infrared 27 . Metamaterial can also be applied in various applications: as dual tunable absorbers 28 of different shapes such as chevron 29 and wrench 30 ; chemical sensing 31 ; infrared filter 32 , 33 ; tunable polarizer 34 , microelectromechanical devices 35 ; and polarization-insensitive devices 36 . Nanoparticle can also be used in development of biosensor for applications such as medical diagnostic devices 37 .…”
Section: Introductionmentioning
confidence: 99%
“…The permittivity and permeability of metamaterials can be tailored by properly engineering the geometrical dimensions and material compositions of their subwavelength periodic patterns. They are widely studied to realize thermal emitters and are perfect absorbers for energy harvesting, medical imaging, and high-sensitivity sensing applications [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. By tailoring the geometrical dimensions, metamaterials can be designed to span broad operating wavelengths, including visible [31][32][33], IR [34][35][36][37][38][39], terahertz [40][41][42][43][44], and microwave light [45,46].…”
Section: Introductionmentioning
confidence: 99%
“…Electromagnetic absorber has attracted various interests in recent years due to its numerous applications in solar‐energy harvesting, photon detection, biosensing, and thermal imaging. [ 1–7 ] Many research efforts have been devoted to develop the high‐performance absorber with perfect absorption, [ 8 ] multi‐band absorption, [ 9,10 ] broadband absorption, [ 11 ] polarization‐independent absorption, [ 12 ] and omnidirectional incidence [ 13 ] spanned the entire spectrum. [ 14–17 ] To date, many tuning mechanisms are presented for tunable electromagnetic absorbers using coherent absorption, [ 18 ] semiconductor, [ 19 ] surface plasmon polariton, [ 20 ] and metamaterial.…”
Section: Introductionmentioning
confidence: 99%